2023
DOI: 10.1007/s10896-023-00556-0
|View full text |Cite
|
Sign up to set email alerts
|

Animal Consumption Associated with Higher Intimate Partner Aggression

Abstract: Purpose This brief report examined associations between animal consumption and intimate partner aggression in a sample of undergraduates. Two possible explanatory variables for these associations, depressive symptoms and speciesism, were also examined. Methods Participants included 245 undergraduate students who provided electronic consent and completed a one-time anonymous survey. Results Results indicated that ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The consumption of flavor enhancers such as MSG might also influence behavior depending on the specific food to which it is added, such as meat. It is worth noting that emerging human research has linked higher levels of meat consumption with increased aggression toward an intimate partner (Taft et al 2023). In animal studies, a high-fat, high-chicken-meat diet is associated with disturbances to the gut microbiota (Shi et al 2020); if this research is replicated and extended, researchers should query the types of meat (highly processed, inclusive of dietary excitotoxins?…”
Section: Microbiome and The Legalomementioning
confidence: 99%
“…The consumption of flavor enhancers such as MSG might also influence behavior depending on the specific food to which it is added, such as meat. It is worth noting that emerging human research has linked higher levels of meat consumption with increased aggression toward an intimate partner (Taft et al 2023). In animal studies, a high-fat, high-chicken-meat diet is associated with disturbances to the gut microbiota (Shi et al 2020); if this research is replicated and extended, researchers should query the types of meat (highly processed, inclusive of dietary excitotoxins?…”
Section: Microbiome and The Legalomementioning
confidence: 99%
“…Recent studies have identified associations between meat consumption and aggression (Sachdeva et al, 2018;Taft et al, 2023). On the other hand, studies have shown that concern for and empathy towards animals is positively associated with concern for and empathy towards humans (see Eleonora, 2017).…”
Section: Possibilities Resistances and Hopementioning
confidence: 99%